Testing weight-based conditional discrimination in Goffin’s cockatoos, Cacatua goffiniana - Poppy J. Lambert; Antonia Rippel-Rachle; Alice M. I. Auersperg (PLoS ONE, 2025)
Discrimination learning tasks are a method for investigating species’ perception of and associative learning with a particular stimulus. Goffin’s cockatoos previously required surprisingly few trials to differentiate objects based on weight alone in a simple discrimination task, outperforming primates in other weight discrimination setups. Nevertheless, it was unclear whether the difference in performance was largely based on ability or differences in experimental procedures. Therefore, we tested a group of Goffin’s cockatoos on a weight-based conditional discrimination, like a task previously used with chimpanzees. Similar to the chimpanzees (compared to their first 15 sessions), none of our subjects reached above-chance levels of performance in the present study. The contrasting performance of our cockatoos in the two weight discrimination studies are in line with the idea that conditional discriminations are more cognitively demanding than simple discriminations. Our results do not support the notion of a distinct difference between birds and primates in their arbitrary discrimination learning abilities with weight cues. However, further research on this question (we suggest with simple discrimination formats) would be necessary.